1959
DOI: 10.2136/sssaj1959.03615995002300060022x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Iron, Aluminum and Humic Acid on Phosphorus Fixation by Organic Soils

Abstract: Studies were conducted comparing the effects of Fe, Al, and humic acid on P fixation in two organic soils which had undergone different degrees of decomposition. It was shown that organic soils fix P similarly to other reported P‐fixing systems. Fe and/or Al additions increased phosphate fixation while humic acid resulted in an apparent negative absorption. Further, humic acid prevented absorption of P in the presence of limited quantities of Fe and Al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

1963
1963
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 0 publications
3
22
0
Order By: Relevance
“…Nevertheless, as the P-PAE and Prhizon were even lower than the control, the use of this product for agricultural crop production is discouraged, especially on P-rich soils, so as to avoid further soil P accumulation. On the other hand, the product's ability to fixate P is of increasing interest for forestry on drained peat-and wetlands to reduce P leaching and increase P adsorption (Larsen et al, 1959;Nieminen et al, 2003Nieminen et al, , 2011Scheffer and Kuntze, 1999;Silfverberg and Hartman, 1999). A long study period will, however, be required because of the slow development of active root/mycorrhiza associations that may be necessary for significant P release (Nieminen et al, 2003(Nieminen et al, , 2011.…”
Section: Iron Phosphate Sludgementioning
confidence: 99%
“…Nevertheless, as the P-PAE and Prhizon were even lower than the control, the use of this product for agricultural crop production is discouraged, especially on P-rich soils, so as to avoid further soil P accumulation. On the other hand, the product's ability to fixate P is of increasing interest for forestry on drained peat-and wetlands to reduce P leaching and increase P adsorption (Larsen et al, 1959;Nieminen et al, 2003Nieminen et al, , 2011Scheffer and Kuntze, 1999;Silfverberg and Hartman, 1999). A long study period will, however, be required because of the slow development of active root/mycorrhiza associations that may be necessary for significant P release (Nieminen et al, 2003(Nieminen et al, , 2011.…”
Section: Iron Phosphate Sludgementioning
confidence: 99%
“…Steenari et al 1998, Larsson and Westling 1998, Perkiömäki and Fritze 2003. In general, peaty soils have low contents of P-sorbing Al and Fe hydroxides and oxides (Cuttle 1983, Nieminen andJarva 1996) and a number of studies have shown that the application of Al or Fe together with P increases adsorption and reduces leaching from organic soils (Larsen et al 1959, Fox and Kamprath 1971, Scheffer and Kuntze 1989. However, the P adsorption capacity of the native Al and Fe present in the soil before ash application may also increase after ash fertilization because of the liming effect.…”
Section: Introductionmentioning
confidence: 99%
“…The application of Fe or Al together with P has been shown to be an effective means of increasing adsorption and reducing leaching from peat soils (Larsen et al 1959, Fox and Kamprath 1971, Scheffer and Kuntze 1989, Nieminen 2002. It is not known, however, whether the phosphate fertilizers sorped by Al and Fe remain available to trees.…”
Section: Discussionmentioning
confidence: 99%